Telomere & Early Senescence Trophoblast in Preeclampsia: Impact & Opportunity - Prof. Adhi Pribadi (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
In general, and with numerous studies, telomeres in trophoblast cells tend to be significantly shorter in preeclampsia compared to normal pregnancies. This telomere shortening occurs due to high oxidative stress and premature cellular senescence in the placenta.What are Telomeres? Telomeres are the final sections of chromosomes, consisting of repeating DNA strands. Telomeres function as protective "caps" that maintain the stability of DNA and chromosomes, preventing them from being easily damaged or broken apart during cell division. Each time a cell divides, the telomeres shorten slightly. If the telomeres become too short, the cell will no longer be able to divide and will decease. This is a key indicator of biological aging.